Public sector managers: managing innovation and risks - Sharma, Dinesh Raj (1999)
It is argued that there are certain features and organisational contexts of the public sector requiring different managerial behaviours. In public sector organisations many managerial activities are the province of `non-managerial managers'. The risk-taking factors in the public sector are not comparable to that in the private sector. It is believed that the wealth, equity and accountability are the major concerns of the public sector management, whereas, profit and return on investment are the prime concerns of the private sector. Almost all public sector managers adopt a strategy for survival rather than for performance in the Nepalese public sector. Non-interference in the executive function is critically important factor in order to enable the managers to be innovative and risk taking in the public sector. In brief, the paper discusses on managerial potentialities within the public sector and suggests to use the existing, apparent and disguised managerial capability for the betterment of the public sector in Nepal. - Reproduced
Keywords: Managers; Public sector